2021
DOI: 10.3390/md19020118
|View full text |Cite
|
Sign up to set email alerts
|

α-Conotoxins and α-Cobratoxin Promote, while Lipoxygenase and Cyclooxygenase Inhibitors Suppress the Proliferation of Glioma C6 Cells

Abstract: Among the brain tumors, glioma is the most common. In general, different biochemical mechanisms, involving nicotinic acetylcholine receptors (nAChRs) and the arachidonic acid cascade are involved in oncogenesis. Although the engagement of the latter in survival and proliferation of rat C6 glioma has been shown, there are practically no data about the presence and the role of nAChRs in C6 cells. In this work we studied the effects of nAChR antagonists, marine snail α-conotoxins and snake α-cobratoxin, on the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 101 publications
1
8
0
Order By: Relevance
“…we also performed targeted oxylipin profiling, and identified activated AA metabolism by CHI3L1. The compounds of the cascade, such as prostaglandin E2 and leukotrienes, is known for their capability supporting cancer cell survival and proliferation [ 46 ]. Here we concluded that CHI3L1 promotes ROS synthesis and disturbs lipid homeostasis, thus accelerating HCC progression.…”
Section: Discussionmentioning
confidence: 99%
“…we also performed targeted oxylipin profiling, and identified activated AA metabolism by CHI3L1. The compounds of the cascade, such as prostaglandin E2 and leukotrienes, is known for their capability supporting cancer cell survival and proliferation [ 46 ]. Here we concluded that CHI3L1 promotes ROS synthesis and disturbs lipid homeostasis, thus accelerating HCC progression.…”
Section: Discussionmentioning
confidence: 99%
“…The application of α-conotoxins PnIA, RgIA, ArIB[V11L,V16D], or MII together with either baicalein or indomethacin to Ehrlich carcinoma enhanced the antitumor activity several-fold ( Osipov et al, 2020 ). However, while baicalein exerted antiproliferative and cytotoxic effects also on C6 glioma cells, α-Ctx and α-conotoxin RgIA on the contrary promoted proliferation of these cells ( Terpinskaya et al, 2021 ). Thus, further research is required to elucidate the role of nAChRs in different tumor cell lines and environments.…”
Section: Discussionmentioning
confidence: 99%
“…655 α-Conotoxins promote the proliferation of C6 glioma cells in vitro . 656 Synthesised 3/4- and 3/6-, but not 3/7-, loop-size variants of α-conotoxins GI and MI are potent inhibitors of muscular nAChR's. 657 Both the α4/7-conotoxin CIC (venom of C. catus ) and an N -terminus truncated mutant selectively inhibit α3β2 and α6/α3β2β3 nAChR, suggesting the N -terminal tail can accommodate structural changes without any effect on observed receptor activity.…”
Section: Molluscsmentioning
confidence: 99%